ADIKTOLOGIE Journal 2020
DOI: 10.35198/01-2019-002-0002
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook Ads as a Recruitment Strategy for Web Surveys on Drugs: Experience from the European Web Survey on Drugs

Abstract: BACKGROUND: General population surveys present a useful tool for getting information on drug use prevalence, but they often fail to reach a sufficient number of users, which is required to get detailed information on use patterns or other characteristics. Web surveys, especially when they use social networking sites, might present a complementary mechanism for getting a better picture of drug use by reaching hard-to-reach populations. AIM: The main objective of this study was to examine Facebook advertisements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This might reflect differences in motivation to participate in online surveys, but also variations in preferences of social networks among different age groups in included countries. More information on characteristics of participants is available in Jerković, Lotar Rihtarić, Van Laar, Horvat, Udrisard, and Matias (2019). Other research also showed that Facebook is especially effective in targeting young people (e.g.…”
Section: Figure 2 Costs Per Click and Per Participant In Eur In Faceb...mentioning
confidence: 99%
See 1 more Smart Citation
“…This might reflect differences in motivation to participate in online surveys, but also variations in preferences of social networks among different age groups in included countries. More information on characteristics of participants is available in Jerković, Lotar Rihtarić, Van Laar, Horvat, Udrisard, and Matias (2019). Other research also showed that Facebook is especially effective in targeting young people (e.g.…”
Section: Figure 2 Costs Per Click and Per Participant In Eur In Faceb...mentioning
confidence: 99%
“…Furthermore, convenience sampling was open to self-selection bias, and therefore our results cannot be generalizable. In addition, convenience sampling methods that do not set demographic quotas while targeting might result in a substantial number of homogeneous participants, which could have been the case in this survey (Jerković et al, 2019). This is because Facebook's marketing algorithms maximizes clicks on the advertisement by sending it to the users that the algorithm recognizes as those who will click on an advertisement with high probability.…”
Section: Conclusion Commentsmentioning
confidence: 99%